Sol-gel synthesis and characterization of iron- and nitrogen-doped titanium dioxide (TiO2) photocatalysts for enhanced rhodamine B degradation - Ilma Maulidina; Dwi Febrianti; Priyan Prayogo; Rifqi Almusawi Rafsanjani; Iin Riananda; Ridho Hidayat; Laila Khafidatul Rosidah; Jesica Violina; Posman Manurung; Herman; Yayat Iman Supriyatna; Okta Ferli Suryadi; Indra Pardede (Scientific Nexus, 2025)
Rhodamine B is a carcinogenic synthetic dye extensively used in textile and food industries, requiring effective removal from wastewater. Conventional titanium dioxide (TiO₂) photocatalysts demonstrate limited effectiveness under solar irradiation due to ultraviolet light activation requirements. This study evaluated strategic modification of TiO₂ electronic structure through low-concentration iron and nitrogen doping to enhance visible-light photocatalytic performance for rhodamine B degradation. Nanoscale TiO₂ materials were synthesized using sol-gel methodology and doped with iron and nitrogen precursors. Comprehensive characterization employed X-ray diffraction, ultraviolet-visible spectroscopy, and scanning electron microscopy to evaluate structural, optical, and morphological properties. Structural analysis confirmed preservation of anatase crystalline phase with 12.94 nanometer average crystallite size. Optical characterization revealed bandgap modifications from 3.27 eV for pure TiO₂ to 2.85 eV for iron-doped and 3.25 eV for nitrogen-doped samples. Nitrogen-doped TiO₂ achieved superior rhodamine B degradation efficiencies of 94.16% under ultraviolet irradiation and 83.34% under visible light, significantly outperforming pure and iron-doped materials. Enhanced performance resulted from optimized charge carrier dynamics balancing improved light harvesting with reduced electron-hole recombination. These findings establish a practical approach for developing cost-effective, solar-responsive photocatalysts for sustainable wastewater treatment applications.